Features of the state of the chromosomal apparatus of spouses with disorders of reproductive function - Feskov, O.; Zhylkova, Ye.; Rudenko, V.; Chumakova, N.; Yegunkova, O. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
Chromosomal anomalies are the most frequent reason of infertility in the world. This is one of the reasons for abortion in the early stages, stillbirth or the birth of a child with multiple malformations. The general level of chromosomal aberrations in the population is 0.5-3.0 %, while among people with impaired fertility this level ranges from 2.9 to 14%. The results of karyotyping of 1024 patients with problems of reproduction function, which appealed to the Center of Human Reproduction «Clinic of Professor Feskov O.» in the period from 2009 to 2014, were presented in the article. For the cytogenetic research of patients, metaphase chromosomes were used. Samples were obtained from culture of peripheral blood according to standard technique. For staining of chromosomes slides GTG-method and CBG-method were used. Analysis of slides was carried out in accordance with the International system of the cytogenetic nomenclature. Different types of chromosomal aberrations have been detected in the karyotypes of the patients in 6.05% cases, in population this value is 0.5–3.0 %. This increase in the number of changes in karyotype in patients with infertility in comparison with the population level is statistically significant (р˂0.05). There are numerical chromosome abnormalities, structural chromosome rearrangements and chromosomes polymorphisms in the patients. Among identified changes the chromosomes polymorphisms are more frequent, it total 2.4% in our group. Among them 1.25% cases of increase in length of satellite on the short arm of acrocentric chromosomes, 0.67% – increase in length of centromeric heterochromatin, 0.38% – increase in length of heterochromatin on the long arm of chromosomes 9, 16, Y. Structural chromosome rearrangements were found in 2.11% patients, among them inversions – 0.86%, Robertsonian translocations and reciprocal translocations – 0.58% і 0.1% respectively, insertions – 0.1%, additional material of unknown origin – 0.1% and marker chromosomes – 0.1%. Numerical chromosomes abnormalities have been detected in 1.63% cases (17 patients out of 1042) – among them Klinefelter syndrome – 0.67% patients, and cases with different mosaic karyotype for sex chromosomes – 0.96%. So it is recommended to carry out karyotyping of couples with infertility.